Tauroursodeoxycholic acid regulates macrophage/monocyte distribution and improves spinal microenvironment to promote nerve regeneration through inhibiting NF-κB signaling pathway in spinal cord injury - Hou, Yonghui; Zhang, Yage; Ma, Lin; Luo, Dan; Wang, Wanshun; E., Shunmei; Huang, Chengxi; Hou, Yu; Chen, Shudong; Zhan, Jiheng; Xu, Liangliang; Lin, Dingkun (Frontiers in Pharmacology, 2025)
IntroductionFollowing spinal cord injury (SCI), blood-borne monocytes infiltrate the spinal cord, differentiate into macrophages, and dominate the lesion site. Inflammatory responses mediated by macrophages determine nerve regeneration and functional recovery after SCI. Tauroursodeoxycholic acid (TUDCA) shows a neuroprotective effect in different SCI animal models. However, the underlying mechanism of TUDCA regulating monocytes/macrophages to impact nerve regeneration after SCI has not been elucidated clearly. This study aims to investigate the effect of TUDCA on monocyte/macrophage distribution and nerve regeneration in the subacute stage of SCI.MethodsTranswell analysis, Bromodeoxyuridine (BrdU) staining, and TUNEL staining were performed to evaluate the effect of TUDCA on regulating the inflammatory response to impact spinal neural stem cells (NSCs) proliferation and migration, spinal neuron survival, and axon degeneration in vitro. H&E staining, RNA sequencing, and a series of immunofluorescent staining were performed to investigate the pathological progress, gene expression changes, monocytes/macrophages distribution, and nerve regeneration after TUDCA treatment in SCI mice.ResultsWe found TUDCA restored spinal NSCs migration and proliferation and reduced spinal NSCs and neurons apoptosis and axon degeneration by regulating inflammatory response in vitro. TUDCA treatment promoted wound healing, down-regulated genes related to inflammatory response, and up-regulated genes related to spinal cord development in SCI mice.ConclusionsOur study provided evidence that TUDCA treatment regulated monocyte/macrophage distribution and improved the microenvironment to promote nerve regeneration in SCI mice.